FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM PEMBELIAN PRODUK KENDARAAN BERMOTOR MERK YAMAHA JUPITER Z PADA CV. MAHKOTA MOTOR PEKANBARU - Adri Candra; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Consumer behavior is very important for a company, by studying consumer behavior will help the company in its market to identify market segments will be more effective. Studying consumer behavior will also be able mengetahaui how consumers in the purchase decision process and the factors that influence it. The purpose of this study was to determine the basic behavior of consumers in the purchase of a motorcycle Yamaha Jupiter Z on the CV. Mahkota Motor pekanbaru.The method used in this research is descriptive quantitative method. Sampling techniques that are used is accidental sampling with a population of 326 people and the sample size was 77 respondents. Data were obtained through interviews and questionnaires that measured using a Likert scale.The results of this study indicate that factors influencing consumer behavior in purchasing products Yamaha Jupiter Z motor vehicle on a CV. Mahkota Motor show agreed criteria.Keywords : Consumer behavior, consumer behavior factors